2019
DOI: 10.1140/epjds/s13688-019-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying human mobility resilience to extreme events using geo-located social media data

Abstract: Mobility is one of the fundamental requirements of human life with significant societal impacts including productivity, economy, social wellbeing, adaptation to a changing climate, and so on. Although human movements follow specific patterns during normal periods, there are limited studies on how such patterns change due to extreme events. To quantify the impacts of an extreme event to human movements, we introduce the concept of mobility resilience which is defined as the ability of a mobility system to manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…Therefore, we aimed to observe the evacuation behaviors of residents in these states. Previous studies [14,15] show that evacuation mobility follows the Levy-Walk model, where short distance trips are the majority. Thus, we add the states that share a border with FL, GA and SC; and purchased all tweets with spatial bounds set to cover the states of North Carolina (NC), Tennessee (TN), Southern Carolina (SC), Georgia (GA), Alabama (AL), and Florida (FL).…”
Section: Data Collectionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, we aimed to observe the evacuation behaviors of residents in these states. Previous studies [14,15] show that evacuation mobility follows the Levy-Walk model, where short distance trips are the majority. Thus, we add the states that share a border with FL, GA and SC; and purchased all tweets with spatial bounds set to cover the states of North Carolina (NC), Tennessee (TN), Southern Carolina (SC), Georgia (GA), Alabama (AL), and Florida (FL).…”
Section: Data Collectionmentioning
confidence: 96%
“…Large-scale spatiotemporal data such as GPS, cell phone data and geotagged social media data enable researchers to model population evacuation behaviors at societal scales [13,14]. Most of recent studies aim to reveal the common patterns of evacuation trajectories, for example the distance and regularity of evacuees' mobility trajectories [14,15]. However, these studies fail to provide detailed evacuation behaviors with specific spatial information, such as evacuation destinations, which is necessary to improve evacuation management.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the power of social media to connect a large group within a population has drawn significant attention toward using social media platforms for disaster management (Keim & Noji, 2010;Sadri, Hasan, & Ukkusuri, 2019;Tang, Zhang, Xu, & Vo, 2015). Studies have analyzed social media data for understanding human mobility and resilience during a disaster (Roy, Cebrian, & Hasan, 2019;Wang & Taylor, 2014). Kryvasheyeu et al (2015) proposed that social media users can be considered as early-warning sensors in detecting and locating disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Misra et al (2014) studied the best practices of using social media data and found that almost every state department of transportation, many public transit agencies, and airports have a social media presence, indicating a dramatic shift on how agencies interact with its customers. Tweets posted during various disasters have been analyzed to extract useful information about the disaster (Imran et al, 2013;Roy, 2018;Roy and Hasan, 2018), individual user behavior (Rashidi et al, 2017;Roy et al, 2019), address the reliability of posted messages (Mendoza et al, 2010), relate with established statistics (Culotta, 2010), increase awareness (Huang et al, 2010), assess damage (Kryvasheyeu et al, 2016), and even to detect earthquake (Earle et al, 2011). Recent studies have investigated on how to understand the interplay among user activities, network properties, and the attention received in social media and to identify factors for successful crisis communication in emergency situations (Sadri et al, 2017a,b).…”
Section: Related Workmentioning
confidence: 99%